2020
DOI: 10.1016/s2666-5247(20)30005-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of mcr-1 prevalence and mcr-1-positive Escherichia coli after the cessation of colistin use as a feed additive for animals in China: a prospective cross-sectional and whole genome sequencing-based molecular epidemiological study

Abstract: Background The global dissemination of colistin resistance encoded by mcr-1 has been attributed to extensive use of colistin in livestock, threatening colistin efficacy in medicine. The emergence of mcr-1 in common pathogens, such as Escherichia coli, is of particular concern. China banned the use of colistin in animal feed from May 1, 2017. We investigated subsequent changes in mcr-1 prevalence in animals, humans, food, and the environment, and the genomic epidemiology of mcr-1-positive E coli (MCRPEC).Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 31 publications
7
97
1
1
Order By: Relevance
“…As a result, China banned the use of colistin as a feed additive for animals on 1 May 2017 ( 13 ). It has been reported that the mcr-1 prevalence decreased significantly in national pig farms after the ban of colistin in animal feed ( 14 ). A reduction in the mcr-1 -positive E. coli population size following the colistin ban could also be expected in Père David’s deer, which warrants further surveillance.…”
Section: Observationmentioning
confidence: 99%
“…As a result, China banned the use of colistin as a feed additive for animals on 1 May 2017 ( 13 ). It has been reported that the mcr-1 prevalence decreased significantly in national pig farms after the ban of colistin in animal feed ( 14 ). A reduction in the mcr-1 -positive E. coli population size following the colistin ban could also be expected in Père David’s deer, which warrants further surveillance.…”
Section: Observationmentioning
confidence: 99%
“…Accumulated evidence showed that banning of colistin in animal feed efficiently restricted mcr-1 prevalence, not only in animals but also in humans and the whole ecosystem in China [2][3][4]. However, our previous study showed that a low proportion of Escherichia coli carrying chromosomally-encoded mcr-1 continually existed in the ecosystem [4], which was sporadically reported by other studies as well [9][10][11]. On account of the plasmid that could be lost under certain circumstances due to instability, the chromosomally-encoded events could stabilize the heritage of mcr-1, threatening the intervention of colistin stewardship.…”
Section: Short Reportmentioning
confidence: 99%
“…The emergence and rapid dissemination of plasmid-mediated mobile colistin resistance gene ( mcr - 1 ) have become a severe threat to public health [ 1 ]. The predominant carriers of mcr - 1 were IncX4, IncI2, and IncHI2 plasmids, which are transferable and adaptive plasmid types with broad host range and contributed to the spread of mcr - 1 among various sources and bacterial species [ 2 4 ]. Besides, recombination of transposons, especially Tn 6330 (IS Apl1 - mcr - 1 - pap2 -IS Apl1 ), the primary vehicle for transmission of mcr - 1 , and phage-like sequences enable mcr - 1 to transfer across plasmids and isolates.…”
Section: Short Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest research showed that the mcr-1 prevalence has been dramatically decreased to a low prevalence. 36 The rational use of antimicrobials should be considered as a key measure to prevent the rising of antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%